SENTIMENTALISM IN THE 18 CENTURY: SAMUEL RICHARDSON AND LAURENCE STERNE (Ustozlar uchun, 2025)
This article examines the literary movement of sentimentalism in the 18th century, focusing on the works of Samuel Richardson and Laurence Sterne. Sentimentalism emphasized emotion, moral reflection, and the cultivation of sympathy in readers as a response to the rationalism of the neoclassical period. Richardson’s epistolary novels, such as Pamela, highlight virtue, emotional sensitivity, and moral instruction, whereas Sterne’s Tristram Shandy combines sentiment with humor, digression, and narrative innovation. Both authors contributed significantly to the development of the English novel by engaging readers’ empathy and moral consciousness. Their works demonstrate how literature can evoke emotional and ethical reflection, shaping the novel as a tool for social and moral education.